The Strategy of CHSE Implementation in Kampung Lauk Babakan, Bogor - Rima Pratiwi Batubara; Aditya Sugih Setiawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Ministry of Tourism and Creative Economy (Kemenparekraf) issued a program of cleanliness, health, safety, environment sustainability or better known as CHSE. The CHSE concept is considered to be one of the solutions for Kampung Lauk Babakan because its components support environmental sustainability and the comfort of the actors. The management and community of Kampung Lauk Babakan do not yet know the concept of CHSE. The problem of Kampung Lauk Babakan is also important to address considering that this area is planned to be integrated with the Situ Gede tourist area and broadly develop the area. The CHSE implementation strategy in Lauk Babakan Village is carried out by using a SWOT analysis approach. The strategy used to implement CHSE is to improve the quality of human resources, strengthen regional institutions, determine and disseminate policies and regulations, develop regional objects and increase marketing and promotion.